Damage Analysis of Lahat Roads – Fence Natural From Endikat Bridge To Go To Depati H. Duaji Lintas Street Pagaralam – Lahat - Andy Kurniawan; Sartika Nisumanti; Khodijah Al Qubroh (Journal of Applied Engineering and Technological Science (JAETS), 2022)
Roads have a very important role in human life. For the present and the future, in the era of industrialization, trade and public transportation, transportation of goods and services. This study aims to determine the type of damage that occurs on the pavement surface, pavement conditions and the necessary actions on the pavement conditions of the Lahat-Pagaralam section of the bridge from Endikat to the Depati H. Duaji road of Pagaralam-Lahat by using the Pavement Condition Index method ( PCI). There are 10 types of damage to the Lahat - Pagaralam crossing from the Endikat bridge to the Depati H. Duaji Lintas Pagaralam road, namely crocodile cracks by 20.39%, obesity by 3.95%, basins by 0.66%, curl by 0.66 %, edge cracks of 3.29%, longitudinal/transverse cracks of 5.26%, fillings of 55.92%, aggregate wear of 1.32, holes of 7.24% and grooves of 1.32%. The average pavement condition index (PCI) for the Lahat - Pagaralam section from the Endikat bridge to the Depati H. Duaji Pagaralam road section is 82.63% which is included in the Very Good category. The repair methods that can be carried out are the P2 (Local Asphalt Laburan) repair method, the P5 repair method (Hole filling) and the P6 repair method (Alignment).